Multi-omics approach in tea polyphenol research regarding tea plant growth, development and tea processing: current technologies and perspectives - Jingwen Li; Yu Wang; Joon Hyuk Suh (Food Science and Human Wellness)
Polyphenols are one of the most important metabolites in tea due to their unique biological activities and health benefits, arousing great attention of researchers to investigate biochemical mechanisms of polyphenols during tea plant growth, development and tea processing. Although omics has been used as a major analytical platform for tea polyphenol research with some proven merits, a single-omics strategy remains a considerable challenge due to the complexity of biological system and functional processes of tea in each stage of tea production. Recent advances in multi-omics approaches and data analysis have enabled mining and mapping of enormous number of datasets at different biological scales from genotypes to phenotypes of living organisms. These new technologies combining genomics, metagenomics, transcriptomics, proteomics and/or metabolomics can pave a new avenue to address fundamental questions regarding polyphenol formation and changes in tea plants and products. Here, we review recent progresses in single- and multi-omics approaches that have been used in the field of tea polyphenol studies. The perspectives on future research and applications for improvement of tea polyphenols as well as current challenges of multi-omics studies for tea polyphenols are also discussed.